2019
DOI: 10.1002/jsfa.10166
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of two arbuscular mycorrhizal fungal inocula to improve saline stress tolerance in lettuce plants by changes of antioxidant defense mechanisms

Abstract: BACKGROUND: Arbuscular mycorrhizal (AM) fungi establish symbioses with most agricultural plants and improves growthunder soil stress conditions. The present study aimed to evaluate the functional contribution of 2 AM fungal inocula (a native consortium isolated from saline soils of the Atacama Desert, 'HMC', and a reference inoculum Claroideoglomus claroideum, 'Cc') on the growth and antioxidant compounds of two cultivars of lettuce (Lactuca sativa cvs. 'Grand Rapids' and 'Lollo Bionda') at increasing salt str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 52 publications
8
63
1
Order By: Relevance
“…Both inoculums employed in this study lead to lower levels of phenolic compounds in lettuce when they were grown under saline conditions. They proposed that the microorganism can be useful for reducing the negative effect of salinity on the lettuce growth, which would be achieved by affecting the glycoside synthesis pathways, thus explaining the lower levels of phenolic compounds [16]. These results are in accordance with those reported in the present study so, it seems that HUTR05 inoculum can favor the growth of lettuce under saline conditions although the alleviation of saline stress may negatively affect the phenolic compound levels.…”
Section: Total Phenolic Contentsupporting
confidence: 92%
See 2 more Smart Citations
“…Both inoculums employed in this study lead to lower levels of phenolic compounds in lettuce when they were grown under saline conditions. They proposed that the microorganism can be useful for reducing the negative effect of salinity on the lettuce growth, which would be achieved by affecting the glycoside synthesis pathways, thus explaining the lower levels of phenolic compounds [16]. These results are in accordance with those reported in the present study so, it seems that HUTR05 inoculum can favor the growth of lettuce under saline conditions although the alleviation of saline stress may negatively affect the phenolic compound levels.…”
Section: Total Phenolic Contentsupporting
confidence: 92%
“…These authors also reported significant phenolic content variety effects depending on the inoculum [3], highlighting again that the efficiency of inoculation can change according to the lettuce variety. Similarly, Santander and co-workers [16] have reported that the concentration of phenolic compounds in lettuce leaves was significantly affected not only by the cultivar and the inoculation with arbuscular mycorrhizal but also by the salinity level in growth conditions [16]. Both inoculums employed in this study lead to lower levels of phenolic compounds in lettuce when they were grown under saline conditions.…”
Section: Total Phenolic Contentsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar transcriptional regulation of antioxidant enzyme transcript levels (cAPX, CAT, GR, and MnSOD) decreased 0.4-fold H 2 O 2 and 3.9-fold NO in hydrogen sulfide (H 2 S)-primed strawberry plants under NaCl stress in a hydroponic setup [184]. Santander et al [185] reported that arbuscular mycorrhizae-induced increased SOD, CAT, and APX activities in 40 and 80 mM NaCl-stressed cucumber. Moreover, Moringa oleifera leaf extract (6%) or Glycyrrhiza glabra root extract mitigates salt stress by upregulating antioxidants in wheat and bean (P. vulgaris) [186,187].…”
Section: Antioxidant Defense In Plants Under Salinitymentioning
confidence: 91%
“…All the extracts were dried in a rotary evaporator and re-suspended in 1 mL of the mobile phase (water:acetonitrile:formic acid; 92:3:5; v / v / v ). Quantification of phenolic compounds was carried out in a Shimadzu HPLC system (Tokyo, Japan) equipped with a quaternary LC-20AT pump with a DGU-20A5R degassing unit, a CTO-20A oven, a SIL-20a autosampler and an UV-vis diode array spectrophotometer (SPD-M20A), according to the described by Santander et al [ 50 ]. HPLC-DAD system coupled to a mass spectrometer (QTrap LC/MS/MS 3200 Applied Biosystem MDS Sciex system (Foster City, CA, USA)) was used to obtain the identity assignments [ 51 ].…”
Section: Methodsmentioning
confidence: 99%